Problems of the time of foundation and the tectonic evolution of the Onega — Kandalaksha paleorift in the light of the data of isotopic geochronology - A. S. Baluev; S. Yu. Kolodyazhny; E. N. Terekhov; V. A. Lebedev; P. A. Serov (Известия высших учебных заведений: Геология и разведка)
Kandalaksha graben, located in the water-area of the White sea, is a part of the Onega-Kandalaksha paleorift of the Riphean time of foundation. It is filled with the terrigenous formations of the Terskaya suites ranging from 3 to 8 km by depth, while the age of the rocks of the Terskaya suite is still controversial, and according to different sources, ranges from 1300 to 670 Ma. This means that the time of the formation of Kandalaksha Graben is not precisely defined. In 2016, on the Tersky Bank of the Kola Peninsula, a sample of sandstones of the suite was selected. The age of the rock of 1390±25 Ma, i.e. the boundary of the early and middle Riphean, was determined by the K-Ar isotope method.. This corresponds to the time of the beginning of the stretching of the lithosphere and continental rifting. Quartz-microcline metasomatites formed on sand-shale spit of Terskaya suite in the zone of amethyst deposit of Cape Korablik gave the age of 821±170 Ma, determined by Sm-Nd method, and fluorite of the same rocks gave the age of 690±71 Ma. The last value is close to the age of the basalts from the Onega depression, defined by the same method. These data correspond to the momentum of stretching of the passive Timan margin of the Baltic area at the end of the late Riphean.